Drugs misuse among children: measuring the level of parents' awareness on their children's behavioural change / Afifah Hanani Rosdi - Rosdi, Afifah Hanani (Faculty of Communication and Media Studies, 2019)
A survey was carried out to gather information on knowledge, attitudes and awareness of parents on children in relation to drug misuse matters. The respondents were selected through purposive sampling method. Significantly, parents are aware of reasons why drug addicts find it difficult to change their habits, mainly lacking motivation to stop taking drugs and that drug addicts do not have the power to control themselves. There was an agreement that unfulfilled needs such as 'not being respected or recognised for one’s capabilities' and 'not being loved or treated fairly by parents', were among causes of drug abuse. This study referred to Social Bonding Theory as its reference to compare the results of the findings with the existing theory. Meanwhile, based on Raosoft Calculator software, since the population size of the study is 8.15 million, hence 90°A> level of confidence was used to describe the amount of uncertainty the researcher can tolerate. The response distribution is 700/0 whereby it is the probability distribution of the response (target) variable. Thus, as calculated in the software, the recommended sample size is 228 respondents. In this study, the researcher managed to gather 242 respondents in order to identify the level of awareness of parents on their children's behavioural change. The R2 obtained = 0.401 defines that 40.1 % of the amount of variance in the awareness of parents can be explained by the independent variables.